2017
DOI: 10.1038/srep45179
|View full text |Cite|
|
Sign up to set email alerts
|

Significantly Enhanced Energy Storage Density by Modulating the Aspect Ratio of BaTiO3 Nanofibers

Abstract: There is a growing need for high energy density capacitors in modern electric power supplies. The creation of nanocomposite systems based on one-dimensional nanofibers has shown great potential in achieving a high energy density since they can optimize the energy density by exploiting both the high permittivity of ceramic fillers and the high breakdown strength of the polymer matrix. In this paper, BaTiO3 nanofibers (NFs) with different aspect ratio were synthesized by a two-step hydrothermal method and the pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 62 publications
(25 citation statements)
references
References 35 publications
0
25
0
Order By: Relevance
“…Figure a shows the finite element calculation results of the distribution of the electric field for the region near a BaTiO 3 fiber in a P(VDF‐HFP)/BaTiO 3 fiber (2.5 vol. %) matrix . The aspect ratio of the fibers is 3.5 and the fibers are orientated at 30° to the applied field.…”
Section: Dielectric Materials Based On Pvdf‐based Polymers For Energymentioning
confidence: 99%
See 2 more Smart Citations
“…Figure a shows the finite element calculation results of the distribution of the electric field for the region near a BaTiO 3 fiber in a P(VDF‐HFP)/BaTiO 3 fiber (2.5 vol. %) matrix . The aspect ratio of the fibers is 3.5 and the fibers are orientated at 30° to the applied field.…”
Section: Dielectric Materials Based On Pvdf‐based Polymers For Energymentioning
confidence: 99%
“…c) Effect of aspect ratio of BaTiO 3 fibers on the energy density of the composites. d) Effect of volume fraction of BaTiO 3 fibers on the energy density of the composites . Reproduced with permission.…”
Section: Dielectric Materials Based On Pvdf‐based Polymers For Energymentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, using planar Ti‐film as the Ti source hinders complete transformation and limits BTO formation to the vicinity of the film surface. Using a very similar approach, BTO samples with fiber morphology were obtained from K 2 Ti 6 O 13 and Na 2 Ti 3 O 7 fibers, under hydrothermal conditions . In a very recent study, Nageri and Kumar used anodized TiO 2 nanotube arrays as a template to prepare well‐ordered, vertically aligned BTO nanotube arrays by the hydrothermal method for visible light photocatalytic degradation of MB .…”
Section: Introductionmentioning
confidence: 99%
“…[18][19][20][21][22][23][24] Of particular, previous research has confirmed that high aspect ratio onedimensional (1D) ceramic nanofillers, such as barium titanate (BT) and lead zirconate titanate (PZT) nanowires, can efficiently enhance the dielectric constant and energy density of polymer nanocomposites when compared to their corresponding spherical particles. [25][26][27][28][29][30][31] This is due to the fact that the ferroelectric ceramic nanowires possess larger dipolar moment, which could enhance D max of these nanocomposites at a lower volume fraction, also benefiting the E b . 32 However, the large P r of the ferroelectric ceramic fillers was employed, leading to more electric energy being stored in the form of P r , thus the polymer nanocomposites filled with traditional ferroelectric fillers (e.g., BT and PZT) cannot be extracted a high energy density during the discharging process.…”
Section: Introductionmentioning
confidence: 99%